Educational administration, policy, and reform : research and measurement - Hoy, Wayne K.; Miskel, Cecil G. (Research and theory in educational administration., 2004)
This book series on Theory and Research in Educational Administration is about understanding schools. We welcome articles and analyses that explain school organizations and administration. We are interested in the "why" questions about schools. To that end, case analyses, surveys, large data base analyses, experimental studies, and theoretical analyses are all welcome. We provide the space for authors to do comprehensive analyses where that is appropriate and useful. We believe that the Theory and Research in Educational Administration Series has the potential to make an important contribution to our field, but we will be successful only if our colleagues continue to join us in this mission.